2016
DOI: 10.7897/2321-6328.04540
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Evaluation of Zimad-E-Jarb in Jarb (Scabies): A Single Blind Randomized Controlled Study

Abstract: Scabies is a contagious skin disease, caused by Sarcoptes scabiei which affects around 300 million populations every year globally affecting mostly the children; but can occur in any age group and the incidence is similar in both sexes. The present clinical trial was designed to evaluate the efficacy of Zimad-e-Jarb in the management of Jarb on scientific parameters. It was a single blind randomized controlled study and was conducted on 30 patients of Jarb at National Institute of Unani Medicine, Bangalore. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The study revealed that Zimad-e-Jarb is effective in Jarb (Scabies) in terms of itching, erythema, papules and number of lesions without any side effect 34. Wang and Borison were concluded a study that copper sulphate has emetic property35 .…”
mentioning
confidence: 99%
“…The study revealed that Zimad-e-Jarb is effective in Jarb (Scabies) in terms of itching, erythema, papules and number of lesions without any side effect 34. Wang and Borison were concluded a study that copper sulphate has emetic property35 .…”
mentioning
confidence: 99%